Feeling good the science of well-being - Cloninger C Robert (Oxford OUP, 2004)
Its describes a way to coherent living that satisfies these strong basic needs through growth in the uniquely human gift of self-awareness. The scientific findings that led Dr Cloninger to expand his own views in a stepwise manner during 30 years of rese
Keywords: Consciousness; Happiness; Health; Love; Mind and body; Personality; Philosophy of mind; Psychiatry; Psychophysiology